2004
DOI: 10.1097/01.tp.0000107284.04969.5c
|View full text |Cite
|
Sign up to set email alerts
|

Topical photodynamic therapy in the treatment of actinic keratoses and Bowen’s disease in transplant recipients

Abstract: Topical PDT with 20% 5-ALA is an effective and safe treatment for AK and BD in immunosuppressed TR, with initial response rates comparable with those in immunocompetent patients. It is particularly useful in TR because of the possibility for repeated treatment of large lesional areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 25 publications
8
124
0
1
Order By: Relevance
“…Of the 37 post-PDT SCC, 30 (81%) were invasive and 7 (19%) were microinvasive and, of the 48 SCC outside a PDT field, 34 (74%) were invasive and 12 (26.09%) microinvasive. However, no experimental studies have demonstrated an excess risk of developing SCC after PDT in that patient population (14,(27)(28)(29). In addition, as we observed more SCC outside the PDT field than in the PDT field, this emphasizes that our population had a higher risk of SCC development.…”
Section: Resultssupporting
confidence: 49%
“…Of the 37 post-PDT SCC, 30 (81%) were invasive and 7 (19%) were microinvasive and, of the 48 SCC outside a PDT field, 34 (74%) were invasive and 12 (26.09%) microinvasive. However, no experimental studies have demonstrated an excess risk of developing SCC after PDT in that patient population (14,(27)(28)(29). In addition, as we observed more SCC outside the PDT field than in the PDT field, this emphasizes that our population had a higher risk of SCC development.…”
Section: Resultssupporting
confidence: 49%
“…83 A comparison of MAL-PDT with topical 5-FU in only five OTRs with SCC in situ is discussed in section 11.2.…”
Section: 78-82mentioning
confidence: 99%
“…AK clearance with ALA-PDT appears equally effective in immunosuppressed and immunocompetent people. 100 In one study of OTRs with a prior history of SCCs, ALA-PDT was administered on a cyclic basis with pretreatment curettage of hyperkeratotic AKs. Patients received up to 14 treatments over 2 years.…”
Section: Aks In Organ Transplant Recipientsmentioning
confidence: 99%